Application Of, And Experience With, An Electronically-Controlled Hydraulic Piling Hammer ? 1 ? Introduction - D. Arentsen (Deep Foundations Institute, 1987)
Changing environmental laws, new operating requirements and the increasing accuracy with which the bearing capacity of driven piles can be calculated have all led to the development of hydraulic piling hammers, some very primitive, others very advanced. Users find it difficult to decide which model is the most suitable, because the specifications are neither uniform nor unamiguous. There are no standard specifications and, moreover, the majority of hammers are suitable only for a limited range of applications. For the user, however, it is important to choose a hammer which will meet future as well as current requirements and will not quickly become obsolete or be unsuitable for a particular job.